2013
DOI: 10.1371/journal.pone.0071945
|View full text |Cite
|
Sign up to set email alerts
|

Why Movement Is Captured by Music, but Less by Speech: Role of Temporal Regularity

Abstract: Music has a pervasive tendency to rhythmically engage our body. In contrast, synchronization with speech is rare. Music’s superiority over speech in driving movement probably results from isochrony of musical beats, as opposed to irregular speech stresses. Moreover, the presence of regular patterns of embedded periodicities (i.e., meter) may be critical in making music particularly conducive to movement. We investigated these possibilities by asking participants to synchronize with isochronous auditory stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 70 publications
1
30
0
Order By: Relevance
“…Notably, beat perception is often accompanied by a synchronized motor response. For example, the temporal features of musical patterns and their temporal regularity are particularly conducive to movement . Our proclivity to move to music manifests when we move to its beat, which can happen spontaneously or deliberately, by foot or hand tapping, and in dance or synchronized walking.…”
Section: Human and Nonhuman Studies Of Vocal Rhythmmentioning
confidence: 99%
“…Notably, beat perception is often accompanied by a synchronized motor response. For example, the temporal features of musical patterns and their temporal regularity are particularly conducive to movement . Our proclivity to move to music manifests when we move to its beat, which can happen spontaneously or deliberately, by foot or hand tapping, and in dance or synchronized walking.…”
Section: Human and Nonhuman Studies Of Vocal Rhythmmentioning
confidence: 99%
“…Third, music is fundamentally rhythmic, containing repeated patterns of sound and therefore involves recurring patterns of rhythmic movements. Taken together, such repetitive joint rhythmic action may be especially effective in tapping interpersonal similitude and coordination (e.g., Dalla Bella et al, 2013), which could potentially foster intersubjectivity (Feldman, 2007; Gallagher, 2008; Gallagher and Hutto, 2008), in part because it contains basic imitative elements (Meltzoff, 2007, 2013; Saby et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…How, then, does dance actually affect individuals’ auditory perception of sound? Human body movement is closely related to the perception of rhythm [ 12 , 13 ]. Previous experiments have shown that the manner in which people move their bodies to music affects their auditory perception of the rhythm structure [ 14 ].…”
Section: Introductionmentioning
confidence: 99%